Prediction of Moments in the Particles on Demand Method for LBM (Communications in Computational Physics, 2023)
PonD is a method to extend LBM calculations to arbitrary ranges of Machnumber and temperature. The current work was motivated by the issue of mass, momentum and energy conservation in the PonD method for LBM. The collision guarantees their conservation, thus, the study involves all aspects of the streaming step:both coordinate and velocity space discretizations, gauge transfer method, resolutionof the scheme implicitness. After obtaining the expressions for the change of momentsin the system in a time update of the scheme, it was found that the scheme can be formulated as explicit in some cases. Thus, we found the sufficient conditions to makePond/RegPonD computations explicit and mass, momentum, and energy conserving.The scheme was implemented in the explicit form, and validated for several test cases.